THE EFFECT OF THE COMBINATION OF WHATSAPP AND FACEBOOK SOCIAL MEDIA ON KNOWLEDGE MASTERY AND ATTITUDES OF OBESE TEENAGERS IN BALONGPANGGANG DISTRICT, GRESIK REGENCY - Ningtiyas, Meilinda Eka Surya (Jurnal Gizi dan Kesehatan Nusantara, 2023)
Social media is one of the social networking sites that exist in information and communication technology today, including WhatsApp and Facebook. In this study WhatsApp and Facebook media were used as media for nutrition education. The purpose of this study was to determine the effect of nutrition education through a combination of WhatsApp and Facebook social media on the acquisition of knowledge and attitudes of obese adolescents, as well as to determine the effectiveness of using the combination of WhatsApp and Facebook media. This type of quantitative research uses a quasy experimental design method with a Nonequivalent control group research design. The sampling technique used purposive sampling so that 68 respondents were obtained which were divided into 2 experimental groups and a control group. Data collection techniques using knowledge test instruments and attitude questionnaires. Analysis using Paired Sample T-Test, Independent Sample T-Test and NGain Score. The results of this study indicated that nutrition education through a combination of WhatsApp and Facebook media had an effect on obesity adolescents' mastery of knowledge (p=0.007), nutrition education with a combination of WhatsApp and Facebook media had an effect on obese adolescents' attitudes (p=0.020), Nutrition education through a combination of WhatsApp media and Facebook is quite effective in increasing mastery of knowledge and less effective in increasing the attitude of obese adolescents. This needs to be done in combination with other social media that teenagers often use to get information other than Facebook, because the use of Facebook media is rarely used by teenagers to get information.